SOLUTIONS TO REDUCE WATER POLLUTION AT METAL CRAFT VILLAGE OF THANH THUY COMMUNE, THANH OAI DISTRICT, HANOI CITY - Thi Huong, Tran; Thi Bich Hao, Nguyen; Thi Thuy An, Thai; Thi Ngoc Bich, Nguyen; Thanh Thuy, Kieu (Journal of Forestry Science and Technology, 2020)
The metal craft village in Thanh Thuy commune produces a variety of products, but the machines and production processes are outdated. All metal craft production wastewater is discharged directly to Nhue River, the section flowing through Thanh Thuy commune, thus polluting surface and ground water. Research results show that surface water in the area is seriously polluted by Zn, in which 80% of the samples have a Zn content exceeding the permissible limit from 23.3 to 74 times, and 100% of the samples contain COD exceeding the allowed limits by 1.6 to 3.2 times, the metals of Mn, Fe, and Cr show signs of pollution in some local ponds and lakes. Groundwater is seriously polluted by metals such as Zn and Fe, in which 100% of the groundwater samples have Fe contents exceeding the permitted limit from 2.25 to 17.71 times, 100% of the groundwater samples have Zn contents exceeding the permissible limit from 1.3 to 8.3 times, and other pollutants are at high risk of pollution. In order to improve the water quality, the study has proposed some integrated solutions that combine many management, planning, and techniques measures, and environmental education. Particularly, the study focuses on solutions for cleaner production and waste generation prevention at sources by implementing good internal management, replacing raw materials; optimizing the production process; and on-site recovery and reuse. In addition, local authorities should select locations to build wastewater treatment systems, and implement communication solutions to raise awareness of local people on environmental and water protection.